Concrete pry-out failure of single headed stud anchors after fire exposure: Experimental and numerical study. (1st April 2021) - Tian, Kaipei; Ožbolt, Joško
Highlights: After only 15 min of fire 50% of reduction of reference resistance can occur. Concrete surface spalling leads to strong reduction of the pry-out resistance. The cold state resistance is critical compared to the hot state resistance. Microplane based thermo-mechanical model for concrete can well replicate the experimental results. Abstract: In the present study the pry-out failure of single headed stud anchors after fire exposure is investigated experimentally and numerically. For the fire load the standard ISO 834 fire curve was employed. The influences of concrete compressive strength, embedment depth and fire duration on the load-bearing behaviour of anchors are investigated. The numerical simulations were conducted using the thermo-mechanical model that was implemented into a three-dimensional finite element (3D FE) code. The constitutive law for concrete is the temperature dependent microplane model. The numerical results were first verified based on the performed experimental tests. The influence of surface spalling of concrete on the pry-out failure resistance was investigated numerically. Subsequently, further parametric studies were carried out. It is shown the employed numerical modelling technique can successfully predict the pry-out failure mode and the load bearing behaviour of anchors after fire exposure. The experimental and numerical results show that the pry-out failure capacity of headed stud anchors is strongly reduced after fire exposure. Nevertheless, the cold state (after cooling) resistance, which is lower than the hot state resistance, is concluded to be critical for concrete pry-out failure. This is due to the fact that cooling process leads to further damage of concrete. It is demonstrated that the current design formula needs to be improved.